The role of large-conductance, calcium-activated potassium channels in a rat model of trigeminal neuropathic pain. (January 2015) - Liu, Cai-Yue; Lu, Zhan-Ying; Li, Na; Yu, Li-Hua; Zhao, Yun-Fu; Ma, Bei
Background: Trigeminal neuralgia is a disorder of paroxysmal and severely disabling facial pain and continues to be a real therapeutic challenge. At present there are few effective drugs. Here the aim of this study was to investigate the role of BKCa channels in trigeminal neuropathic pain. Methods: Rats were divided into two groups: a sham and a chronic constriction injury of infraorbital branch of trigeminal nerve (ION-CCI) group. Nociceptive behavior testing, immunohistochemistry, RT-PCR, Western blotting and whole-cell patch clamp recording were used. Results: Relative to the sham group, rats with ION-CCI consistently displayed lower mechanical pain thresholds in the vibrissal pad region from day 6 to 42 after ION-CCI operation. ION-CCI induced a significant down-regulation of BKCa channels both in mRNA and protein levels in the ipsilateral trigeminal ganglion (TG), a lower threshold intensity of action potential, and decreased total BKCa currents in cultured TG neurons. TG target injection of NS1619 (20–100 µg), an opener of BKCa channels, dose-dependently increased the mechanical pain threshold, which was blocked by the BKCa channel inhibitor iberiotoxin (IbTX, 20 µg). NS1619 (10 µM) significantly increased the mean threshold intensities of action potentials in ION-CCI rats, while failing to affect those in the sham rats. The levels of phosphorylated extracellular signal-regulated kinase (ERK), p38 and c-Jun N-terminal kinases (JNK) in TG were significantly increased after ION-CCI operation. The ERK1/2 antagonist U0126, p38 antagonist SB203580 and JNK antagonist SP600125 significantly reversed the facial mechanical allodynia in ION-CCI rats. However, the ERK1/2 antagonist U0126, p38 antagonist SB203580 but not JNK antagonist SP600125 significantly increased BKCa currents in ION-CCI TG neurons. Conclusions: Our results indicate the important involvement of mainly ERK and p38 MAPK pathways in modulating BKCa channels in ION-CCI TG neurons. BKCa channels represent a new therapeutic target for the clinical treatment of trigeminal neuropathic pain.